The Influence of Good University Governance, Tuition Fees, Infrastructure Facilities, and The Quality of Lecturer Teaching on The Quality of Educational Services (Case Study: UIN Syarif Hidayatullah Jakarta) - Irfan, Mohamad Ali; Hidayat, Taufik; Afriana, Gina (LPPM Universitas PGRI Sumatera Barat, 2023)
This study aims to determine the influence of each variable, namely good university governance (GUG), education costs, facilities, infrastructure, and teaching quality, on the quality of education services at Syarif Hidayatullah State Islamic University Jakarta. The research uses quantitative methods with associative properties data obtained through direct distribution of questionnaires to respondents. Data analysis uses data normality and linearity tests for data requirements that are typically distributed and linear. Hypothesis testing used partial correlation coefficient analysis and multiple regression correlation coefficient analysis. Good university governance has a significant effect on the quality of education services; education costs significantly affect the quality of education services; facilities and infrastructure significantly affect the quality of education services; lecturer teaching quality significantly affects the quality of education services.